Television communication: verbal behavior of the participants in the TV programs - Khmel, Lizaveta R. (Journal of the Belarusian State University. Journalism, 2019)
The television communication is considered as a special type of public communication. The participants (addresser and addressee) of the TV programs are stood out and their verbal behavior on TV screen is characterized. For example, within the Belarusian TV content polite, aggressive and tolerant modes of the speech behavior are analysed and appropriate stratеgies and tactics of speech interaction are given.